Wokół bohatera literackiego najnowszej prozy polskiej: kilka uwag o outsiderskiej przestrzeni - Figa, Anna (Poznańskie Studia Polonistyczne. Seria Literacka, 2014)
<span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: 'ＭＳ 明朝'; mso-fareast-theme-font: minor-fareast; mso-fareast-language: PL; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The article indicates the features of space ascribed to the literary protagonists who can be regarded as outsiders. Three types of figures of an “outsider out of necessity” have been selected: a rogue/scoundrel, a homosexual and a chav. For each of these figures—and they are characteristic for the Polish latest prose—distinctive dominant space is attributed, which defines, in different ways, and simultaneously brings out the limiting one-dimensionality and, tragic in its expression, the seclusion associated with the condition of “outsiders out of necessity”. With reference to a rogue/scoundrel especially important is flattening (certain “one-dimensionality”) of the disintegrating landscape. In the case of homosexuals there dominates a closed space of one’s own house (flat). For chavs, in turn, characteristic are labyrinth-like districts of urban ghettos.